KEPEMIMPINAN VISIONER DALAM PENDIDIKAN KARAKTER DI ERA SUPER SMART SOCIETY 5.0 - Mahyuni, Rivana Dinda; Nurul Haq; Ulfa Muthmainnah; Siti Jumaliyah; Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research discusses visionary leadership in character education in the Super Smart Society 5.0 era. Leadership in this research is based on technology which is increasingly developing rapidly until it reaches the 5.0 era. So in this case, a visionary leader is really needed in character education for the young generation living in this era. The purpose of this research is to find out what methods and solutions will be provided by educational leaders, in the sense of educators, regarding the character education of today’s young generation to keep pace with developments in increasingly modern times. The hope in the future is that the character education provided can be in line with technological advances in the 5.0 era. This research uses a qualitative method with a type of library research, usually used for searches that are detailed, complete, and explain the material in depth. Important information in this journal is quoted from printed books, digital books, and journal articles related to the topics discussed. The results of research regarding visionary leadership in character education in the Super Smart Society 5.0 era it is highly hoped that a leader will have a vision for the future to be able to implement character education for students. Because the era of society 5.0 apart from having enormous potential benefits, it also poses significant risks. If it is not handled carefully by the nation’s generations, it can endanger human life.